The effect of learning styles and student learning activities using the course review horay model on indonesian language learning outcomes of students at SD Negeri 02 Wanarejan, Pemalang regency - Maya Damayanti; Joko Sulianto; Ngatmini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to determine the effect of learning styles and learning activities on Indonesian language learning outcomes and the achievement of learning mastery in the Indonesian language after the Course Review Horay model is implemented. The research was conducted on grade VI students at SD Negeri 02 Wanarejan. The research approach used was qualitative, with a survey research design. Data were collected through questionnaires, documentation, and tests. Data analysis was performed using multiple linear regression analysis, the paired sample t-test, and the independent sample t-test. The study's results indicate that learning styles affect Indonesian language learning outcomes by 24.1%, while learning activities affect 22.3%. Additionally, the combined effect of learning styles and learning activities on Indonesian language learning outcomes among grade VI students at SD Negeri 02 Wanarejan is 46.8%. The conclusion of this study indicates that learning styles and learning activities affect Indonesian language learning outcomes among grade VI students at SD Negeri 02 Wanarejan. Based on the pre-test and post-test evaluation, all students achieved learning mastery in the Indonesian language after the CRH model was implemented with the support of Question Card media.